FAKTOR YANG MEMPENGARUHI HASIL PENJUALAN USAHA DODOL DI DESA PASAR BENGKEL KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Aprialicia Lumban Gaol (Visi Sosial Humaniora, 2021)
This study aims to analyze the effect of capital, labor, and length of business on dodol sales results. The sample in this study was 46 business actors based on predetermined criteria using the random sampling method. The data analysis technique used is multiple linear regression analysis using the SPSS version 23 application. The results of this study indicate that capital, labor, and length of business have a positive and significant effect on the sales of Dodol Business in Pasar Bengkel Village, Perbaungan District, Serdang Bedagai Regency. In the test of the coefficient of determination before the toll road that the capital, labor, and length of business is 0.787. So this means that sales results can be explained by capital, labor, and length of business by 78.7% and the remaining 21.3% is influenced by factors not examined. And after the toll road, it shows that the capital, labor, and length of business are 0.872. So this means that sales results can be explained by capital, labor, and length of business by 87.2% and the remaining 12.8% is influenced by factors not examined. Thus the linear regression model can be considered appropriate.